Evaluasi Implementasi Kebijakan Transaksi Non-Tunai dalam Konteks Pengelolaan Keuangan Daerah: Studi Kasus di Kota Solok-Sumatera Barat - Budi Febrian Wijaya; Suhairi Suhairi; Vima Tista Putriana (Universitas Batanghari Jambi, 2021)
This study aims to evaluate the implementation of non-cash transactions in regional financial management. This research method is a qualitative method with a approach multicase studies. Data collection through interviews, observation and documentation is then processed through data reduction, data presentation and drawing conclusions. Data analysis through the Government Internal Control System approach. The informants of this study consisted of regional financial managers. The results showed that the implementation of non-cash transactions was carried out in stages, there was diversity in implementation, had an impact on the efficiency of administration time, budget, accountability and transparency of cash management and decreased the number of audit findings, but the implementation of non-cash transactions had not had an impact on the recording process of financial statement transactions. accrual-based, efficient audit process time, unorganized administration of financial management accountability, weak control function of OPD Heads, lack of stakeholder commitment, financial management regulations and audits have not been updated, there are no strict sanctions for violations. The obstacles faced are incomplete banking services, making requests if the transfer is different from the bank and the length of time for handling the problem.